2014
DOI: 10.1177/070674371405900405
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Alcohol and Drug Dependence

Abstract: Objective: Our study sought to identify sociodemographic, clinical, life perception, and service use characteristics that distinguish new cases of people dependent on substances from the general population; and to determine predictors of substance dependence over a 2-year period. Variables that differentiate people dependent on substances according to sex and age were also assessed. Methods:Among 2434 people who took part in an epidemiologic catchment area health survey at baseline, 2.2% were identified with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…In contrast, men meeting criteria for SAD were more likely to report dating-related fears, have comorbid externalizing disorders, and to also use alcohol and illicit drugs for symptom relief [90]. Although data from an epidemiologic catchment area health survey (n=2434) found that being male, younger, feeling stigmatized, and scoring higher on impulsiveness were predictors of substance dependence, it also revealed that females meeting criteria for substance dependence were more likely to have comorbid SAD than males with substance dependence [91]. In adolescent girls with SAD, however, drug use was noted to be less likely in a community sample [92].…”
Section: Sex Differences In Sadmentioning
confidence: 97%
“…In contrast, men meeting criteria for SAD were more likely to report dating-related fears, have comorbid externalizing disorders, and to also use alcohol and illicit drugs for symptom relief [90]. Although data from an epidemiologic catchment area health survey (n=2434) found that being male, younger, feeling stigmatized, and scoring higher on impulsiveness were predictors of substance dependence, it also revealed that females meeting criteria for substance dependence were more likely to have comorbid SAD than males with substance dependence [91]. In adolescent girls with SAD, however, drug use was noted to be less likely in a community sample [92].…”
Section: Sex Differences In Sadmentioning
confidence: 97%
“…Research has long posited a host of factors that are associated with drug use (Fleury, Grenier, Bamvita, Perreault, & Caron, 2014; Kirkcaldy, Sifen, Surall, & Bischoff, 2004). Experimenting with substances begins as early as adolescence (Conner, Hellemann, Ritchie, & Noble, 2010) as children seek thrill in risk-taking behavior (Arnett, 1992).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The majority of previous studies which examined predictors of posttreatment relapses in patients with alcohol dependence showed that relapse is a complex and dynamic event that appears to be determined by biological, psychological, and social factors, and an interaction among these [4,15,16]. Literature which focused on socio-demographic factors found that males of a lower age, with a low educational level, unemployment and low socio-economic level, seem to be negatively associated with alcohol-related outcomes [14,16,21,22,23]. Moreover, several studies found that clinical aspects such as dependence severity [13], amount of alcohol consumption [16], polysubstance abuse [4], and a comorbid medical condition [23] are relevant prognostic factors for relapse.…”
Section: Introductionmentioning
confidence: 99%